New Generation of Clinical Epigenetics Analysis and Diagnosis for Precision Medicine - Pengtao Song; Biaoru Li (Diagnostics, 2025)
Following the application of epigenetic and epigenomics research into tumor diseases, cardiovascular disease, diabetes, hereditary diseases, and rare diseases, in vitro diagnostics (IVD) epigenetic and epigenomics are increasingly employed for those patients. Here, we review a clinical sampling of epigenetics and epigenomics from patients. We then present procedures, including the detection procedure of clinical epigenetic approaches from clinical samples, clinical epigenomic methods applied to those samples, the small cell number of epigenetics, and epigenomics. Finally, we present the current IVD of epigenetics and epigenomics used for clinical analysis and diagnosis, along with the development of approaches. To improve clinical study and diagnosis, we also introduce clinical research and clinical applications to develop a more comprehensive strategy to maximize the sensitivity and specificity of the epigenetics and epigenomics analysis and diagnosis.